2014
DOI: 10.3389/fncel.2014.00053
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA dysregulation in spinal cord injury: causes, consequences and therapeutics

Abstract: Trauma to the spinal cord causes permanent disability to more than 180,000 people every year worldwide. The initial mechanical damage triggers a complex set of secondary events involving the neural, vascular, and immune systems that largely determine the functional outcome of the spinal cord injury (SCI). Cellular and biochemical mechanisms responsible for this secondary injury largely depend on activation and inactivation of specific gene programs. Recent studies indicate that microRNAs function as gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 188 publications
(351 reference statements)
0
99
0
Order By: Relevance
“…54 In the laboratory it has been shown to have antiapoptotic and antiinflammatory properties, although its expression decreases 14 days postinsult. 54,59 As a novel therapeutic agent, miR-21 antagomir administered by intrathecal injection decreased recovery of hindlimb motor function, 59 and overexpression of miR-21 has been shown to protect against transient ischemia.…”
mentioning
confidence: 99%
“…54 In the laboratory it has been shown to have antiapoptotic and antiinflammatory properties, although its expression decreases 14 days postinsult. 54,59 As a novel therapeutic agent, miR-21 antagomir administered by intrathecal injection decreased recovery of hindlimb motor function, 59 and overexpression of miR-21 has been shown to protect against transient ischemia.…”
mentioning
confidence: 99%
“…Following injury, the differential expression of miRNAs in the nervous system may play a role in predicting the development of chronic pain [29]. CED has not been explored extensively as a delivery method for miRNAs in the treatment of NP, recent studies have identified several microRNAs including miR-21, miR-486, miR-20 involved in key mechanisms of SCI such as cell death or astrogliosis, direct evidence on the role of miRNAs in SCI is scarce [30]. Furthermore, from clinical perspective, evidence makes it clear that miRNAs may be potent therapeutic tools that can manipulate cell state and molecular processes in order to enhance functional recovery.…”
Section: Additionally There Is a Need To Visualize Target And Contrmentioning
confidence: 99%
“…Could the injured spinal cord also have limited diffusion via CED similar to nerves, needs to confirm. Small silica cannula inserted in peripheral nerve; (10,20,30,40, and 80 ml) of 14C-labeled or gadolinium-labeled albumin were infused unilaterally or bilaterally into the tibial nerves of primates @ 0.5ml/min; and one primate infused bilaterally with gadoliniumbound albumin (40 ml/nerve) underwent MR imaging 16 weeks after infusion.…”
Section: Modeling Ced In the Spinal Cordmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their key roles in the regulation of gene expression, cell differentiation, proliferation and apoptosis, miRNAs have been observed to participate in various neurological diseases (10,11). Furthermore, an increasing number of studies have suggested that miRNA serve an important role in the development of SCI (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%